(untitled) (Research, Society and Development, 2020)
The flour from the pulp of marolo (Annona crassiflora Mart.) is an important source of fiber, however, its use as a food ingredient requires investigation as to its functionality. Thus, this work aimed to evaluate the physical, chemical, nutritional and technological functional properties of the flour obtained from the pulp of marolo, thus verifying its potential application in food products. The analyzes performed on the flour were proximal composition, mineral composition, vitamin C content, total carotenoids, beta-carotene, antioxidant activity and technological functional properties. The flour presented considerable amounts of fibers, especially the insoluble fraction, being 25.47 g.100g-1, 8.57 g.100g-1 for soluble dietary fiber and 34.04 g.100g-1 for total dietary fiber. . The levels of vitamin C and total carotenoids, observed in the flour of the pulp of marolo, were 173.77 mg.100g-1, 0.56 mg.100g-1 and 0.08 mg.100g-1, respectively. The minerals that showed the highest concentration in the pulp flour were phosphorus (1768.53 mg.kg-1) and calcium (1512.73 mg.kg-1). The antioxidant activity was more effective when performed in aqueous extraction. The flour has shown to have important technological functional properties, such as solubility in water and the ability to form emulsion. Therefore, marolo pulp flour has the potential to be commercialized and used in food products in order to improve and enrich its nutritional and technological qualities.